2013
DOI: 10.1007/s11655-013-1503-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Gastrosis No.1 compound on functional dyspepsia of spleen and stomach deficiency-cold syndrome: A multi-center, double-blind, placebo-controlled clinical trial

Abstract: CHM Gastrosis No.1 compound was effective and safe in the treatment of functional dyspepsia with Spleen and Stomach deficiency-cold syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The studies published between 1991 and 2019 were included. Patients had FD, [15][16][17][18][19][20][21][22]13,14,[23][24][25][26][27][28][29][30][31][32] and constipation [56][57][58][59][60][61][62] in 19, 23 and 7 trials respectively. More than 33 different kinds of herbal formulae were tested in the included trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies published between 1991 and 2019 were included. Patients had FD, [15][16][17][18][19][20][21][22]13,14,[23][24][25][26][27][28][29][30][31][32] and constipation [56][57][58][59][60][61][62] in 19, 23 and 7 trials respectively. More than 33 different kinds of herbal formulae were tested in the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…Literature searches identified 3782 potentially relevant titles after elimination of duplicates. After review of the abstracts, 121 full‐text publications were assessed, of which 50 studies were included in this review, involving a total of 7396 participants. As two of the studies shared the same group of patients with two aspects of results reported, so their data was abstracted as one, resulting in totally 49 trials for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) is an effective alternative treatment for FD [8][9][10][11][12][13][14][15][16]. According to TCM, FD is divided into different syndromes based on the clinical symptoms and signs, among which "spleen-deficiency and qi-stagnation" is the most common one [17].…”
Section: Introductionmentioning
confidence: 99%
“… 30 , 31 Some herbal TCM preparations have been shown to have benefit for functional dyspepsia. 32 - 34 Chinese herbal remedies, such as modified Xiao-yao-san and Modified Liu-Jun-Zi decoction might be effective in the treatment of functional dyspepsia. 35 , 36 With regard to TCM treatment for disorders of menstruation, there is some evidence supporting Chinese herbal medicine and acupuncture in treating primary dysmenorrheal.…”
Section: Discussionmentioning
confidence: 99%